Stocks Investment Decision Making Capital Asset Pricing Model (CAPM) - Alecia Ferrari, Erric Wijaya, (Jurnal Manajemen, 2020)
Investment in the capital market generally has a higher rate of return compared to investing in the financial market. Investors sometimes get difficulty in determining which stocks will produce a large return with a small risk. The method used to describe the application of CAPM in this research is done by grouping the efficient, yet inefficient stocks of the banking sector based on the CAPM method. The method in the sample selection was a purposive sample method and obtained 40 banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period of August 2016 - July 2018. The results of this study indicate that there are 31 efficient stocks out of 40 stocks in banking sector. It can be seen that there are 31 banking stocks with a positive average rate of returns and 9 banking stocks with a negative average rate of returns. Meanwhile, the implication of this study is that banking sector shares have efficient shares, since the average rate of return is higher than the expected returns.